IMPROVING THE MECHANISMS OF MILITARY PEDAGOGICAL PERSONNEL TRAINING - Akbarkhodjaev Kamol Abral ogli (Journals Park Publishing, 2025)
Improving the mechanisms of military pedagogical personnel training is one of the most crucial tasks of modern military education. This article analyzes the system of military pedagogy, its distinctive features, and innovative approaches that meet contemporary requirements. Special attention is given to enhancing the professional competence of military personnel, integrating digital technologies into the educational process, and increasing the share of practical training. Additionally, recommendations are provided on utilizing advanced foreign experiences, implementing an individualized approach in military personnel training, and developing the retraining system. The research findings may contribute to improving the efficiency of military pedagogical personnel training and advancing the education system.
Keywords: Military pedagogy, personnel training, innovative education, digital technologies, practical training, professional development.